2014
DOI: 10.15376/biores.9.2.3334-3346
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Miscanthus Pellet Production and Pellet Quality using Response Surface Methodology

Abstract: The Miscanthus sacchariflorus strain Goedae-Uksae 1 has recently been developed as an energy crop, because of its rapid growth, ease of culture, and large size. In this study, Miscanthus pellets were investigated for further practical use of renewable resources. The pellets were produced on a pilot scale and their characteristics and quality were investigated. Moisture content, density of raw materials, and die ratio (L/D) were determined to be the main factors affecting Miscanthus pelletizing. Thus, a central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
3
5
0
1
Order By: Relevance
“…Research on miscanthus biomass pelleting is widely reported in the literature; however, these studies are not comprehensive and do not cover the issues of energy consumption in the compaction process. Moon et al [14] did not obtain pellets of satisfactory quality in the first stage of their research in pilot studies. Mani et al [15] indicated that a lower lignin content and poor bonding between particles during the formation of lignocellulosic granules are the reasons for the lower durability of the obtained pellets.…”
Section: Introductionmentioning
confidence: 95%
“…Research on miscanthus biomass pelleting is widely reported in the literature; however, these studies are not comprehensive and do not cover the issues of energy consumption in the compaction process. Moon et al [14] did not obtain pellets of satisfactory quality in the first stage of their research in pilot studies. Mani et al [15] indicated that a lower lignin content and poor bonding between particles during the formation of lignocellulosic granules are the reasons for the lower durability of the obtained pellets.…”
Section: Introductionmentioning
confidence: 95%
“…It is the largest quantity of biomass residue in the United States as well as in China with over 270 million tons produced annually between the two nations (Kadam andMcMillan 2003, Zhoa andXia 2010). Miscanthus Pellets, derived from Miscanthus sacchariflorus strain GoedaeUksae 1, has recently been developed as an energy crop due to its large size, ease of cultivation and ability to grow rapidly (Moon et al 2014). Wood pellets are sourced from residue associated with harvesting and management of commercial timberlands or non-merchantable biomass from forest inventory, and they are considered as the most common form of pellets used globally for biomass energy production (Perlack et al 2005, Pirraglia et al 2010.…”
Section: Mixture Designsmentioning
confidence: 99%
“…(Nielsen et al, 2020). In the pelleting process of biomass, raw material density, moisture content and die L/D ratio are critical for pellet formation (Moon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%